Building an Energy Consumption Model and Sustainable Economic Growth in Emerging Countries - Desfiandi, Andi; Singagerda, Faurani Santi; Sanusi, Anuar (International Journal of Energy Economics and Policy, 2019)
The research objective is to develop a model of consumption energy, using a model of simultaneous equations with two-stage least square method and some of the assumptions that economic progress will have an impact on increasing energy consumption. The study found several macroeconomic factors such as energy prices, GDP, and exchange rates affecting the level of consumption energy. Whereas the increase in world oil prices and the reduction in the fuel subsidy budget by the government will have an impact on decreasing energy consumption in Indonesia. Forecasting analysis showed that overall energy consumption by all sectors tends to increase, except for biomass consumption by industry and total biomass consumption. In addition, it was also found that there was a small tendency for energy supply to offset the increase in energy consumption in the country. Keywords: Energy, Consumption, Supply JEL Classifications: E6, Q430, Q470, Q480 DOI: https://doi.org/10.32479/ijeep.7353